Effect of E-Leadership and Social Interaction on Managerial Competency of Junior High School Principles - Jumaiyah, Jumaiyah (Journal of Educational Sciences, 2021)
This study aims to analyze the effect of E-Leadership and social interaction both partially and simultaneously on the managerial competence of junior high school principals in Dumai City. The population of this study were 37 people consisting of 22 State Junior High Schools and 15 Private Junior High Schools in Dumai. The sample of this research was a saturated sample, that is, the entire population were sampled. Data collection techniques were using questionnaires for the variables E-leadership, social interaction, and managerial competence of school principals. The data analysis technique used in this research was descriptive statistical analysis and inferential statistical analysis. The results of this study indicate that there is a significant influence between the variable E-Leadership (X1) and social interaction (X2) on the managerial competence of school principals (Y) SMP in Dumai City 19.4%. This means that the better the E-Leadership and social interaction of the principal, the better the managerial competence of the principal.